2010
DOI: 10.1186/1471-2377-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson's disease after tamoxifen treatment

Abstract: BackgroundWomen have a reduced risk of developing Parkinson's disease (PD) compared with age-matched men. Neuro-protective effects of estrogen potentially explain this difference. Tamoxifen, commonly used in breast cancer treatment, may interfere with the protective effects of estrogen and increase risk of PD. We compared the rate of PD in Danish breast cancer patients treated with tamoxifen to the rate among those not treated with tamoxifen.MethodsA cohort of 15,419 breast cancer patients identified from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…We presented the similar, like in PD, clinical gender related observations in WD about the age of symptom onset and neurological signs. In PD (and maybe in WD) the differences in age of onset and symptoms are explained by probably higher (dependent on estrogens) initial striatal dopamine levels in women, what can delay the neurological symptom onset in neurodegenerative disorders [20][21][22][23][24]. It is possible that in women with WD, estrogens can also protect neurons against copper accumulation and the oxidative stress that occurs secondary to this accumulation, leading to less frequent neurological symptoms and forms of disease.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We presented the similar, like in PD, clinical gender related observations in WD about the age of symptom onset and neurological signs. In PD (and maybe in WD) the differences in age of onset and symptoms are explained by probably higher (dependent on estrogens) initial striatal dopamine levels in women, what can delay the neurological symptom onset in neurodegenerative disorders [20][21][22][23][24]. It is possible that in women with WD, estrogens can also protect neurons against copper accumulation and the oxidative stress that occurs secondary to this accumulation, leading to less frequent neurological symptoms and forms of disease.…”
Section: Discussionmentioning
confidence: 93%
“…After oophorectomy, a 36% reduction in dopaminergic neurons was observed in women [11], which can be avoided by supplementation with hormones before the procedure [9]. There are data that women who underwent oophorectomy before the menopause or were treated with tamoxifen (selective estrogen receptor modulator) had an increase risk of parkinsonism [23,24]. The "estrogen hypothesis" about gender influence on PD was confirmed by the Parkinson's Disease on Estrogen Therapy Replacement in the Menopause Years study, which showed women on estrogen replacement therapy (ERT) had an 8 point improvement in the Unified Parkinson's Disease Rating Scale (UPDRS) compared to placebo patients [11].…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, other studies have shown that raloxifene prevents MPTPinduced striatal depletion of dopamine (Grandbois et al, 2000). Thus, the neuro-protective properties of estrogen against PD may be disrupted by tamoxifen therapy and treatment may be associated with an increased rate of PD as has been reported by Latourelle et al (2010).…”
Section: Groupmentioning
confidence: 88%
“…Women have a reduced Parkinson's disease risk compared with age-matched men, a phenomenon attributed by some researchers to the neuroprotective properties of estrogen in Parkinson's disease relevant neurons (11). Tamoxifen, a selective estrogen receptor (ER) modulator given to patients with ER-positive breast cancer, has been reported to increase Parkinson's disease rates (12). Thus, in postmenopausal women, markedly reduced estrogen synthesis may both increase the risk of Parkinson's disease and promote the expression of ER genes in breast tissue to enhance breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%